Pengaruh Kualitas Produk Dan Citra Merek TerhadapKeputusan Pembelian Sepeda Motor Yamaha( studi pada konsumen sepeda motor vixion ) - Setia Budi, Himawan Hanif; , Basworo Dibyo, S.E., M.Si (2017)
The purpose of this study is to analyze the effect of product quality and brand image on the purchase decision of Yamaha vixion motorcycle partially or together. This type of research is a qualitative research, with the population of Yamaha vixion motorcycle consumers as many as 100 people, with a sample of 100 consumers. Sampling using sampling technique saturated or total sampling. Methods of collecting research data using questionnaires with liket scale. Data analysis technique used analysis of data instrument test, classical assumption test, multiple linear regression. Based on the result of calculation from T test, F test, showing the variable of product quality and brand image together have a significant influence to purchasing decision. Coefficient of Determination R² obtained result of 0,288 meaning variable of product and brand image able to explain to variation of change of decision variable purchasing equal to 28,8%, the rest can be explained other variable not found in research model.